Health economic evaluation of screening and treating children with familial hypercholesterolemia early in life: many happy returns on investment?. (25th November 2020) - Ademi, Z; Norman, R; Pang, J; Liew, D; Zoungas, S; Sijbrands, E; Ference, B.A; Wiegman, A; Watts, G
Abstract: Background: There are no studies that have specifically investigated the cost-effectiveness of cascade screening of children for heterozygous familial hypercholesterolemia (FH) and treatment of affected individuals with statins to prevent coronary heart disease (CHD). Purpose: This study explores the cost-effectiveness of this strategy from the perspective of the Australian public healthcare system. Methods: A lifetime Markov model with four health states (Alive without CHD, Alive with CHD, Dead from fatal CHD, and Dead from other causes) was developed to simulate the progression of ten- year-old children screened for FH and treated immediately with statins if found to have FH. The underlying prevalence of FH in this target population was assumed to be 56.8%, and the sensitivity and specificity of testing was 100%. The comparator was usual care, which assumed that subjects started statins spontaneously at a later point or when they experienced a cardiovascular event. The effect of reducing low-density lipoprotein cholesterol (LDL-C) on the risk of a first event at each age assumed that risk was proportional to total lifetime exposure and was implemented using Mendelian randomisation analysis data. Cost and other outcome data were sourced from published sources. Outcome of interests were costs in Australian dollars (AUD), life years gained (LYG) and quality-adjusted life years (QALYs) gained, as well as incremental cost-effectiveness ratios (ICERs) of costs per LYG and per QALY gained. All future costs and outcomes were discounted by 5% annually. Results: Undiscounted results showed that compared with usual care, cascade screening of ten year-old children for FH and initiation of treatment of affected individuals saved 7.77 LYG and 7.53 QALYs per person over a lifetime. With 5% annual discounting, there were 0.97 LYG and 1.07 QALYs gained per person, at an additional cost of 3, 244. These equated to ICERs of 3334 per LYG and 3023 per QALY gained. The equivalent ICERs in USD would be 5089 per LYG gained and 4615 per QALY gained. Sensitivity analysis showed the results to be robust. Conclusions: Compared to usual care, cascade screening of ten year old children for FH and treating affected individuals is likely to be highly cost-effective. Funding Acknowledgement: Type of funding source: None